THE MAIN PROBLEMS OF LIGUADIDACTICS IN ENGLISH AND UZBEK GRAMMAR SYSTEM - Ikromjonova, Shokhsanam Akmaljon kizi (Educational Research in Universal Sciences, 2024)
The science of linguodidactics develops the general laws of the theory of language teaching, that is, it deals with the methodological basis of language teaching / learning. These include issues such as the goals, content, methods (principles), tools, methods of scientific research, and the relationship of language teaching with other disciplines.